2016
DOI: 10.1080/10549811.2016.1202841
|View full text |Cite
|
Sign up to set email alerts
|

The competitiveness of the phytosociological attributes of the protected areas in Bangladesh with that in the other tropical countries

Abstract: Many forest reserves in Bangladesh have been converted to protected areas (PAs) to conserve the forests resources from further depletion. This study has investigated if such initiatives have improved the state of biodiversity of these PAs amid tremendous anthropogenic pressure on forest resources. We have assessed the phytosociological attributes of the PAs in the country through a case study at Kaptai National Park (KNP) and compared the attributes with those of the adjacent areas and of the tropical forests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
(28 reference statements)
0
17
5
Order By: Relevance
“…However, the result of this study showed that the biodiversity status and forests stock condition of community managed forests is still in better condition than other government managed forests in Bangladesh. Hossain et al (2013), Hossain, Hossain, Alam, and Uddin (2015), , Rahman et al (2011), and Rahman et al (2017Rahman et al ( , 2016 conducted different studies in different government managed forests throughout the country to calculate phytosociological attributes and biodiversity indices. Findings of these studies showed the poor diversity than our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the result of this study showed that the biodiversity status and forests stock condition of community managed forests is still in better condition than other government managed forests in Bangladesh. Hossain et al (2013), Hossain, Hossain, Alam, and Uddin (2015), , Rahman et al (2011), and Rahman et al (2017Rahman et al ( , 2016 conducted different studies in different government managed forests throughout the country to calculate phytosociological attributes and biodiversity indices. Findings of these studies showed the poor diversity than our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Basak et al (2014) found a total of 148 plant species belonging to 128 genera under 61 families from a VCF covering only 20 ha area. These findings are the testimony that the biodiversity status of VCFs is still better than the government managed forests (Hossain, Hossain, Salam, & Rahman, 2013;Rahman et al, 2011;Rahman, Mahmud, & Ahmed, 2017;Rahman, Mahmud, Shahidullah, Nath, & Jashimuddin, 2016).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Once this dense sub‐tropical dipterocarp forest reserve was under serious threat of exploitation, and so the government declared it as CWS in 1986 to prevent further degradation and protect the habitat for Asian elephants. Since 2004, the CWS has been managed as an integrated protected area with co‐management under several donors who funded development projects (Nath et al, 2016b; Rahman, Mahmood, Shahidulah, Nath, & Jashimuddin, 2016). At least 440 poor household members (usually one from each household) were engaged initially in the CWS co‐management in seven community patrol groups.…”
Section: Methodsmentioning
confidence: 99%
“…The tree species composition of DHF (56 tree species, 50 genera, 29 families) is closer in relation to tropical forest, i.e. 50 tree species in Rampahar Natural Forest Reserve (Chowdhury et al 2018a), 52 tree species in Kaptai National Park (Rahman et al 2016), 62 tree species in Tankawati natural forest (Motaleb and Hossain 2011). However, DHF also possesses lower tree species in comparison to 107 tree species in Kamalachari natural forest, Rangamati and Bandarban borderline (Hossain et al 2015), 153 tree species in Tropical Forest of Eastern Ghats, India (Reddy et al 2011) and 93 tree species in Chunati Wildlife Sanctuary (Nath et al 2016).…”
Section: Discussionmentioning
confidence: 99%